Factors influencing the adoption of E-Government services: A study among University students - Carlos Alberto Méndez-Rivera; Orfa Nidia Pati\~no-Toro; Alejandro Valencia-Arias; Diana María Arango-Botero (Economies, 2023)
The digitization of government services meets the expectations of the younger population, who are accustomed to widespread ICT use. It offers transparency, speed, efficiency, and trust, supported by international organizations. This research aims to identify the factors that influence the adoption of e-government services among university students affiliated with the District Mayor's Office of Science, Technology, and Innovation in Medellín. The study involved surveying a sample of 403 students to examine their intention to adopt e-government services using structural equation modeling. The results highlight the significant impact of perceived usefulness on attitude towards use and, subsequently, on the intention to use e-government. Notably, subjective norm has the least influence on intent to use. The study also underscores the potential of mobile e-government as a promising option, considering the widespread access to smartphones in emerging economies. Cultural factors, usability, data privacy, lack of trust in governments, and entrenched mentalities emerge as barriers to e-government implementation. In conclusion, the findings shed light on the challenges posed by inadequate infrastructure, digital literacy gaps, resistance to change, and cultural factors that impede e-government adoption. Non-adoption would result in technological setbacks, negative indicators, and inefficiencies. Moreover, recognizing the pivotal role of university students in promoting e-government tools among their peers and relatives, this study emphasizes the importance of their involvement.
Keywords: 330; e-government; student; university; factors; adoption; innovation